World overview of the shrimp market / Appa Rao Maradiah, Normah Mohd. Dali and Lau Too Kya - Maradiah, Appa Rao; Mohd. Dali, Normah; Lau, Too Kya (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
This paper briefly discusses an overview of world market demand and the supply of shrimp and its prospects. World demand for shrimp depends on income, population growth, falling prices, changes in taste with regard to seafood and the availability of substitute seafood products. The estimated demand increases by 3.5 percent per annum. About 50 percent of the demand comes from the U.S.A and Japan. About 80 percent of the world supply of shrimp comes from the Asian countries. It is estimated that supply would increase by 60 percent per annum. Since the estimated supply exceeds the estimated demand, prices are expected to fall in the future.